Sosialisasi Potensi Bahaya Geologi dan Mitigasinya di Kecamatan Herlang, Kabupaten Bulukumba, Provinsi Sulawesi Selatan - Hendra Pachri; A. M. Imran; Busthan Azikin; Asri Jaya; Rohaya Langkoke; Ratna Husain; Fauzi Arifin; Safri Burhanuddin; Kaharuddin .; Bahrul Hidayah (Faculty of Engineering UNHAS, 2024)
Bulukumba Regency experienced a geological disaster caused by land movement in the form of landslides and horizontal ground shifts on 24 May 2023. Damage to several government buildings and facilities occurred due to the geological disaster. The government of Bulukumba Regency is aware of the geological disaster that is signalled to continue. Therefore, the Labo-Based Education (LBE) service activity of the Faculty of Engineering was carried out in the Herlang sub-district, Bulukumba Regency. This LBE activity was carried out with the Department of Geological Engineering, Hasanuddin University, and the Government of Herlang District, Bulukumba Regency. This LBE service activity aims to increase the capacity of government and community to introduce geological natural disasters and mitigation efforts. The methods used are making socialisation documents and socialisation of geological disasters to the Herlang sub-district government. Assessment of programme achievement was conducted during the socialisation and by giving short questionnaires before and after the socialisation (post-test). Socialisation on geological hazard potential and mitigation was conducted with the sub-district government, community leaders, community organisations, and the general public, with 46 participants. Based on the questionnaire result, about 85% of the participants understood the geological information in the Herlang sub-district, Bulukumba Regency. The socialisation activity is expected to be sustainable in educating the community to achieve responsive and well-coordinated disaster mitigation.